Determination of Benzocaine, Chlorbutol, P-Dichlorobenzene and Α-Pinene in Pharmaceutical Preparation by Gas Chromatography with Flame Ionization Detector - Saini, Navdeep (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT A simple and rapid method for determination of Benzocaine, chlorbutol, paradichlorobenzene and α-pinene in pharmaceutical preparations was developed and validated using gas chromatography with flame ionization detection (GC-FID). GC separation was performed in about 12 min using a 5% SE-30 column (6ft ×1/8 inch). Nitrogen was used as carrier gas at a flow-rate of 2 ml min-1. After injection of the sample at inlet temperature 225 0C, the temperature of GC oven was as follows: initial temperature was 150 0C, held for 1 min, increased to 180 0C at 50 0C min-1 held for 1 min, and finally to 2500C at 500C min-1 with a final hold of 1.5 min. Calibration curves of benzocaine, chlorbutol, p-dichlorobenzene and α-pinene were linear between the concentration range of 100 to 1000µgml-1, 200 to 2000µgml-1, 32 to 320µgml-1 and 1.2 to 12µgml-1 respectively. The method was found to be specific, precise and accurate. The method was applied for the quality control of commercial ear drop containing Benzocaine, chlorbutol, paradichlorobenzene and α-pinene to quantify the drug and to check the formulation content uniformity.